Images, texts, and marginalia in a "Vows of the peacock" manuscript (New York, Pierpont Morgan Library MS G24) : with a complete concordance and catalogue of peacock manuscripts - Leo, Domenic (Library of the written word ;, 2013)
The ""Vows of the Peacock"" was composed in 1312 in France. One of the extant manuscripts stands out for its beautiful miniatures and scurrilous marginalia (PML, MS G24). It includes a catalogue and concordance of all Peacock manuscripts.